(untitled) (E Global Congress, 2025)
In agricultural practice within the world’s desert regions, the effective utilisation of halophytes plays a crucial role in restoring degraded desert pastures and selecting and cultivating promising high-protein halophytic species. Under the conditions of global climate change, the rational use of the natural flora of halophytes, their selection based on germplasm, the formation of collections, the evaluation of collection samples, and the selection of shrub, semi-shrub, and herbaceous halophytic ecotypes that are both productive and ecologically resilient, allow for achieving improved fodder quality through the application of high-efficiency cultivation technologies.